Genetic susceptibility to idiopathic membranous nephropathy in high-prevalence Area, Taiwan - Chen, Shih-Yin (Biomedicine (Taipei), 2014)
Idiopathic membranous nephropathy (MN) is one common cause of idiopathic nephrotic syndrome in adults; 25% of MN patients proceed to end-stage renal disease. In adults, membranous nephropathy is a lead cause of nephrotic syndrome, with about 75% of the cases idiopathic. Secondary causes include autoimmune disease, infection, drugs and malignancy. Three hypotheses about pathogenesis have surfaced: preformed immune complex, in situ immune complex formation, and auto-antibody against podocyte membrane antigen. Pathogenesis does involve immune complex formation with later deposition in sub-epithelial sites, but definite mechanism is still unknown. Several genes were recently proven associated with primary membranous nephropathy in Taiwan: IL-6, NPHS1, TLR-4, TLR-9, STAT4, and MYH9 . These may provide a useful tool for diagnosis and prognosis. This article reviews epidemiology and lends new information on KIRREL2 (rs443186 and rs447707) polymorphisms as underlying causes of MN; polymorphisms revealed by this study warrant further investigation.